Management of Miller’s Class III Recession Defect with Gingival Unit Transfer-A Promising Technique - Priyalochana Gajendran; Harinath Parthasarathy (Journal of Clinical and Diagnostic Research, 2018)
In all the periodontal plastic surgical procedures, blood supply is the single most significant concern and must be the underlying issue for all the decisions regarding the individual surgical procedure. A major complicating factor is the avascular root surface and many modifications are done to existing techniques to overcome this. One such modification of Free Gingival Graft (FGG) as introduced by Allen and Cohen known as “Gingival Unit Graft” (GUT) where they harvested a palatal graft along with the marginal and the interdental tissue. The present case reports the clinical effectiveness of a novel technique known as gingival unit graft that was evaluated for the management of Miller’s class III gingival recession. This technique showed complete defect coverage and superior aesthetics.